2020
DOI: 10.1021/acs.bioconjchem.0c00078
|View full text |Cite
|
Sign up to set email alerts
|

A Multiparametric Evaluation of Quantum Dot Size and Surface-Grafted Peptide Density on Cellular Uptake and Cytotoxicity

Abstract: Despite the progress in nanotechnology for biomedical applications, great efforts are still employed in optimizing nanoparticle (NP) design parameters to improve functionality and minimize bio-nanotoxicity. In this study, we developed CdSe/CdS/ZnS core/shell/shell quantum dots (QDs) that are compact ligandcoated and surface-functionalized with an HIV-1-derived TAT cell-penetrating peptide (CPP) analog to improve both biocompatibility and cellular uptake. Multiparametric studies were performed in different mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 89 publications
(205 reference statements)
1
14
0
Order By: Relevance
“…The negative control cells treated with QD 608 -RBD alone and the positive control cells treated with Optimem I alone both had equal levels of ATP as reported by the ATPlite luminescence-based reading. These data support the idea that QDs used in this study were not cytotoxic, as previously reported, 33 nor was the RBD domain from SARS-CoV-2 itself.…”
Section: Resultssupporting
confidence: 93%
“…The negative control cells treated with QD 608 -RBD alone and the positive control cells treated with Optimem I alone both had equal levels of ATP as reported by the ATPlite luminescence-based reading. These data support the idea that QDs used in this study were not cytotoxic, as previously reported, 33 nor was the RBD domain from SARS-CoV-2 itself.…”
Section: Resultssupporting
confidence: 93%
“…As a result, in addition to the fact that even the smallest differences in NM physicochemical properties such as size, coatings, synthesis methods, structural defects, concentrations, exposure times, etc . may significantly affect the degree of cell–nano interactions and associated NM toxicity, research groups are employing different methodologies in attempt to evaluate NM toxicity in vitro , leading to discrepancies in published data and irreproducible results . NMs have also been shown to induce toxicity to different cell lines by a variety of mechanisms, either by ROS-mediated apoptosis ( via mitochondrial membrane potential disruption, DNA damage, or activation of MAPK and p53 signaling pathways), endoplasmic reticulum-mediated apoptosis, autophagy, or necrosis, rendering it even more difficult to understand the critical factors involved in their toxicity and to standardize assays, and calling for innovative solutions in the field of nanotoxicology …”
Section: Translational Valuementioning
confidence: 99%
“…The HTS approach developed by Nel and colleagues is a powerful tool for the rapid kinetic analysis of cell–nano interactions, although it requires limited numbers of cells and parameters per analysis to sustain fast data acquisition . HCI, on the other hand, is able to conduct rapid multiparametric acquisitions and automated analyses of images consisting of thousands of cells per condition, generating large data sets that allow the quantitative comparison of the effects of even the smallest differences between NMs on their behavior in various cellular environments. ,, Cellular parameters evaluated using such techniques include viability, proliferation, oxidative stress, damage to cell membrane, mitochondria, lysosomes and DNA, autophagy, cell morphology and cytoskeletal rearrangements, endosomal network changes, among others. These large generated data sets can then be extensively analyzed using statistical tools such as in silico hazard ranking to understand their QSARs, based on which computational paradigms can be developed to predict the toxicological outcome of other NMs both in vitro and in vivo.…”
Section: Translational Valuementioning
confidence: 99%
“…However, this has to be tempered with first building a full understanding of QD toxicity in vivo. Although much work has been done to date on cellular toxicity of QDs [22,[64][65][66], it certainly does not provide the necessary detail needed for in vivo use nor a full appreciation of the cost-benefit analysis that will form the basis for approved use as determined by regulatory agencies.…”
Section: Discussionmentioning
confidence: 99%